KARAKTERISTIK SIFAT FISIKA DAN MEKANIKA KAYU LAMINA KOMBINASI JENIS KAYU SENGON (Paraserianthes falcataria (L.) Nilsen) DAN JENIS KAYU MERBAU (Intsia spp.) - Kusno Yuli Widiati (ULIN: Jurnal Hutan Tropis, 2018)
This study aims to determine the physical and mechanical characteristics of wood lamina combination of sengon wood and merbau with Melamine Urea Formaldehyde (MUF) adhesive. The testing method used is based on the DIN standard. The test results of the average lamina density of 0.58-0.73 g / cm3 at oven drying moisture content. Modulus of Elasticity (MoE), Modulus of Rupture (MoR) and value of compression parallel to grain highest found in the combination of merbau-sengon-merbau-sengon-merbau and the lowest in the combination of sengon-merbau-sengon. While the adhesive shear strength is the highest value in the combination treatment of merbau-merbau and the lowest in the combination of sengon-sengon. Based on the modulus of elasticity (MoE) of sengon treatment as face / back and merbau as core (3 and 5 layers) can be classified into strong class IV-V, merbau as face / back and sengon as core (3 and 5 layers) can be classified into strong class II-III. Modulus of Rupture (MoR) can be classified into strong class II-III and compression parallel to grain into strong class II.